Interactions between climate warming and management actions determining bird community change in protected areas - Leonie Jonas; Jon E. Brommer; Martin Jung; Michal Baláž; John J. Borg; Luka Božič; Preben Clausen; Antoine Derouaux; Koen Devos; Cristian Domșa; Sándor Faragó; Niamh Fitzgerald; et al. (Biological Conservation, 2025)

Protected area characteristics that help waterbirds respond to climate warming - Elie Gaget; Alison Johnston; Diego Pavón‐Jordán; Aleksi S. Lehikoinen; Brett K. Sandercock; Alaaeldin Soultan; Luka Božič; Preben Clausen; Koen Devos; Cristi Domsa; Vitor Encarnação; Sándor Faragó; et al. (Conservation Biology, 2022)
Protected area networks help species respond to climate warming. However, the contribution of a site's environmental and conservation‐relevant characteristics to these responses is not well understood. We investigated how composition of nonbreeding waterbird communities (97 species) in the European Union Natura 2000 (N2K) network (3018 sites) changed in response to increases in temperature over 25 years in 26 European countries. We measured community reshuffling based on abundance time series collected under the International Waterbird Census relative to N2K sites’ conservation targets, funding, designation period, and management plan status. Waterbird community composition in sites explicitly designated to protect them and with management plans changed more quickly in response to climate warming than in other N2K sites. Temporal community changes were not affected by the designation period despite greater exposure to temperature increase inside late‐designated N2K sites. Sites funded under the LIFE program had lower climate‐driven community changes than sites that did not received LIFE funding. Our findings imply that efficient conservation policy that helps waterbird communities respond to climate warming is associated with sites specifically managed for waterbirds.

Benefits of protected areas for nonbreeding waterbirds adjusting their distributions under climate warming - Elie Gaget; Diego Pavón‐Jordán; Alison Johnston; Aleksi Lehikoinen; Wesley M. Hochachka; Brett K. Sandercock; Alaaeldin Soultan; Hichem Azafzaf; Nadjiba Bendjedda; Taulant Bino; Luka Božič; Preben Clausen; et al. (Conservation Biology, 2021)
Climate warming is driving changes in species distributions and community composition. Many species have a so‐called climatic debt, that is, shifts in range lag behind shifts in temperature isoclines. Inside protected areas (PAs), community changes in response to climate warming can be facilitated by greater colonization rates by warm‐dwelling species, but also mitigated by lowering extirpation rates of cold‐dwelling species. An evaluation of the relative importance of colonization‐extirpation processes is important to inform conservation strategies that aim for both climate debt reduction and species conservation. We assessed the colonization‐extirpation dynamics involved in community changes in response to climate inside and outside PAs. To do so, we used 25 years of occurrence data of nonbreeding waterbirds in the western Palearctic (97 species, 7071 sites, 39 countries, 1993–2017). We used a community temperature index (CTI) framework based on species thermal affinities to investigate species turnover induced by temperature increase. We determined whether thermal community adjustment was associated with colonization by warm‐dwelling species or extirpation of cold‐dwelling species by modeling change in standard deviation of the CTI (CTI SD ). Using linear mixed‐effects models, we investigated whether communities in PAs had lower climatic debt and different patterns of community change than communities outside PAs. For CTI and CTI SD combined, communities inside PAs had more species, higher colonization, lower extirpation, and lower climatic debt (16%) than communities outside PAs. Thus, our results suggest that PAs facilitate 2 independent processes that shape community dynamics and maintain biodiversity. The community adjustment was, however, not sufficiently fast to keep pace with the large temperature increases in the central and northeastern western Palearctic. Our results underline the potential of combining CTI and CTI SD metrics to improve understanding of the colonization‐extirpation patterns driven by climate warming.

Membrane vesicle secretion and prophage induction in multidrug‐resistant Stenotrophomonas maltophilia in response to ciprofloxacin stress - Simon Devos; Wouter Van Putte; Jolien Vitse; Gonzalez Van Driessche; Stephan Stremersch; Wim Van Den Broek; Koen Raemdonck; Kevin Braeckmans; Henning Stahlberg; Misha Kudryashev; Savvas N. Savvides; Bart Devreese (Environmental Microbiology, 2017)
Summary Several bacterial species produce membrane vesicles (MVs) in response to antibiotic stress. However, the biogenesis and role of MVs in bacterial antibiotic resistance mechanisms have remained unclear. Here, we studied the effect of the fluoroquinolone ciprofloxacin on MV secretion by Stenotrophomonas maltophilia using a combination of electron microscopy and proteomic approaches. We found that in addition to the classical outer membrane vesicles (OMV), ciprofloxacin‐stimulated cultures produced larger vesicles containing both outer and inner membranes termed outer‐inner membrane vesicles (OIMV), and that such MVs are enriched with cytosolic proteins. Remarkably, OIMV were found to be decorated with filamentous structures identified as fimbriae. In addition, ciprofloxacin stress leads to the release of bacteriophages and phage tail‐like particles. Prophage induction by ciprofloxacin has been linked to pathogenesis and horizontal gene transfer in several bacterial species. Together, our findings show that ciprofloxacin treatment of S. maltophilia leads to the secretion of a heterogeneous pool of MVs and the induction of prophages that are potentially involved in adverse side‐effects during antibiotic treatment.

Reply to the comment on ‘Working with population totals in the presence of missing data comparing imputation methods in terms of bias and precision’ by Bogaart et al. - Thierry Onkelinx; Koen Devos; Ivy Jansen; Hans Van Calster; Paul Quataert (Journal of Ornithology, 2017)

Working with population totals in the presence of missing data comparing imputation methods in terms of bias and precision - Thierry Onkelinx; Koen Devos; Paul Quataert (Journal of Ornithology, 2017)

Sediment-benthos relationships as a tool to assist in conservation practices in a coastal lagoon subjected to sediment change - Carl Van Colen; Dominique Verbelen; Koen Devos; Laure Agten; Joke Van Tomme; Magda Vincx; Steven Degraer (Biodiversity and Conservation, 2014)

Climate change causes rapid changes in the distribution and site abundance of birds in winter - ILYA M. D. MACLEAN; GRAHAM E. AUSTIN; MARK M. REHFISCH; JAN BLEW; OLIVIA CROWE; SIMON DELANY; KOEN DEVOS; BERNARD DECEUNINCK; KLAUS GÜNTHER; KARSTEN LAURSEN; MARC VAN ROOMEN; JOHANNES WAHL (Global Change Biology, 2008)
Detecting coherent signals of climate change is best achieved by conducting expansive, long‐term studies. Here, using counts of waders ( Charadrii ) collected from ca. 3500 sites over 30 years and covering a major portion of western Europe, we present the largest‐scale study to show that faunal abundance is influenced by climate in winter. We demonstrate that the ‘weighted centroids’ of populations of seven species of wader occurring in internationally important numbers have undergone substantial shifts of up to 115 km, generally in a northeasterly direction. To our knowledge, this shift is greater than that recorded in any other study, but closer to what would be expected as a result of the spatial distribution of ecological zones. We establish that year‐to‐year changes in site abundance have been positively correlated with concurrent changes in temperature, but that this relationship is most marked towards the colder extremities of the birds' range, suggesting that shifts have occurred as a result of range expansion and that responses to climate change are temperature dependent. Many attempts to model the future impacts of climate change on the distribution of organisms, assume uniform responses or shifts throughout a species' range or with temperature, but our results suggest that this may not be a valid approach. We propose that, with warming temperatures, hitherto unsuitable sites in northeastern Europe will host increasingly important wader numbers, but that this may not be matched by declines elsewhere within the study area. The need to establish that such changes are occurring is accentuated by the statutory importance of this taxon in the designation of protected areas.

Waterbird communities along the estuarine salinity gradient of the Schelde estuary, NW-Europe - Tom Ysebaert; Peter L. Meininger; Patrick Meire; Koen Devos; Cor. M. Berrevoets; Rob C.W. Strucker; Eckhart Kuijken (Biodiversity and Conservation, 2000)